2022
DOI: 10.1038/s41598-022-07756-6
|View full text |Cite
|
Sign up to set email alerts
|

End-point RT-PCR based on a conservation landscape for SARS-COV-2 detection

Abstract: End-point RT-PCR is a suitable alternative diagnostic technique since it is cheaper than RT-qPCR tests and can be implemented on a massive scale in low- and middle-income countries. In this work, a bioinformatic approach to guide the design of PCR primers was developed, and an alternative diagnostic test based on end-point PCR was designed. End-point PCR primers were designed through conservation analysis based on kmer frequency in SARS-CoV-2 and human respiratory pathogen genomes. Highly conserved regions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In addition, the Ct values were used to determine the number of viruses for each viral load. It was calculated using the following equation, y = −3.2733 x + 38.59, as described in a previous study [ 13 ]. Low viral load was defined as Ct value 30–38 (4.2 × 10 2 –1.5 copies number/mL), moderate as Ct value 25–29 (1.4 × 10 4 –8.5 × 10 2 copies number/mL), and high as Ct value <24 (<2.8 × 10 4 copies number/mL).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the Ct values were used to determine the number of viruses for each viral load. It was calculated using the following equation, y = −3.2733 x + 38.59, as described in a previous study [ 13 ]. Low viral load was defined as Ct value 30–38 (4.2 × 10 2 –1.5 copies number/mL), moderate as Ct value 25–29 (1.4 × 10 4 –8.5 × 10 2 copies number/mL), and high as Ct value <24 (<2.8 × 10 4 copies number/mL).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we did not find any relationship between levels of IgM and IgG and the Ct values. The Ct value is inversely related to the viral load, and every ~3.3 increase in the Ct value reflects a 10fold reduction in starting material (Cruz-Rangel et al, 2022). However, other studies reported that levels of IgG and IgM response could be driven by the viral load (Long et al, 2020;Masiáet al, 2021;Young et al, 2021), but these contrasting results can be explained by the heterogeneity of the studies related to the different characteristics of the study population and/or the methodology used to quantify SARS-CoV-2 and the quality of the sampling (Codina et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 RT-qPCR test provides real-time quantification by first reverse transcribing SARS-CoV-2 RNA into cDNA (RT step) and then performing qPCR, during which a fluorescence signal increases proportionally to the amount of amplified nucleic acid, enabling accurate quantitation of the RNA in the sample (Tom and Mina, 2020). Many qPCR assays involve a Ct cut-off 34 to consider the test positive, allowing the detection of very few starting RNA molecules (Cruz-Rangel et al, 2022).…”
Section: Cycle Threshold Analysismentioning
confidence: 99%
“…When the results of the PCR are analyzed at the end of the reaction it is called end-point PCR (or end-point RT-PCR , ). Typically, this is performed using an agarose gel electrophoresis, where the samples are run together with a ladder to check if the amplicon size (i.e., the number of base pairs, bp) obtained is the one expected .…”
Section: Nucleic Acid Amplification Techniquesmentioning
confidence: 99%